Multi-locus GWAS analysis identifies genomic regions associated with resistance to ergot (Claviceps africana) in sorghum - Dejene Kebede; Patrick Rubaihayo; Geoffrey Tusiime; Arfang Badji; Thomas Odong; Mildred Ochwo-Ssemakula; Richard Edema; Paul Gibson; Isaac Onziga Dramadri (PLoS ONE, 2025)
Deployment of resistant genotypes is one of the major components of ergot disease management in sorghum. Identification of genomic regions and candidate genes associated with resistance to ergot is a key step to facilitate sorghum breeding for resistance to ergot. The objective of this study was to identify genomic regions associated with resistance to ergot in sorghum. A total of 330 lines from the global sorghum association panel (SAP) population genotyped with 114920 genome wide SNP markers were used in this study. The SAP was evaluated for resistance to ergot in two field trials conducted at MUARIK during the first and second seasons of 2020 and 2021, respectively. Six multi-locus genome wide association studies (ML – GWAS) methods were used to identify significant quantitative trait nucleotides (QTNs). ML – GWAS analysis using SAP population detected thirty-eight significant QTNs. Further analysis identified 19 QTNs with relatively higher phenotypic effects ranging from 5–12.7%. Additionally, 47 candidate genes linked with the significant QTNs were detected. Most of the identified genes were involved in several biological processes including DNA and RNA binding, metal ion binding, regulation of transcription and translation and transduction signaling related to defense response against pathogen infections. This study contributes to the identification of significant QTNs and candidate genes associated with resistance to ergot in sorghum.